2020
DOI: 10.56093/ijas.v90i9.106635
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant growth stimulants on nutrients concentration and yield responses of corn (Zea mays)

Abstract: To evaluate the influence of different plant growth stimulants on yield and yield components of corn (Zea mays L), a greenhouse experiment was conducted as a factorial arrangement based on a completely randomized design. The studied treatments (T) were in 8 levels: (T0, control, T1, foliar application of amino acid, T2, foliar application of seaweed, T3, fertigation of humic acid, T4, foliar application of fulvic acid, T5, foliar application of humic acid, T6, inoculation of plant growth-promoting bacteria, T7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The preparations showed an increased growth-stimulating effect in the early stages of plant growth and development. Experiments by H. Ebrahimi et al (2020) proved that the use of plant growth stimulators has improved the use of fertilisers by plants, because they increase the efficiency of nutrient availability and perception by maise plants. Experiments on growth stimulators with corn in China have shown that the growth stimulator EDAH+DA-6 suppresses stem elongation, promotes stem thickening, and increases mechanical strength and the number of vascular bundles (Gong et al, 2021).…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%
“…The preparations showed an increased growth-stimulating effect in the early stages of plant growth and development. Experiments by H. Ebrahimi et al (2020) proved that the use of plant growth stimulators has improved the use of fertilisers by plants, because they increase the efficiency of nutrient availability and perception by maise plants. Experiments on growth stimulators with corn in China have shown that the growth stimulator EDAH+DA-6 suppresses stem elongation, promotes stem thickening, and increases mechanical strength and the number of vascular bundles (Gong et al, 2021).…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%
“…The preparations showed an increased growth-stimulating effect in the early stages of plant growth and development. Experiments by H. Ebrahimi et al (2020) proved that the use of plant growth stimulators has improved the use of fertilisers by plants, because they increase the efficiency of nutrient availability and perception by maise plants. Experiments on growth stimulators with corn in China have shown that the growth stimulator EDAH+DA-6 suppresses stem elongation, promotes stem thickening, and increases mechanical strength and the number of vascular bundles (Gong et al, 2021).…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%